Genetic deletion of the alternative isoform I.1 of HIF-1α in T cells enhances anti-bacterial immune response and improves survival in the model of bacterial peritonitis in mice - Georgiev, Peter (2013)
Hypoxia-adenosinergic suppression and re-direction of the immune response has been implicated in the regulation of anti-pathogen and anti-tumor immunity, with Hypoxia-inducible factor 1α (HIF-1α) playing a major role. In this study, we investigated the role of isoform I.1, a quantitatively minor alternative isoform of HIF-1α, in anti-bacterial immunity and sepsis survival. By using the cecal ligation and puncture model of bacterial peritonitis we studied the function of I.1 isoform in T cells using mice with total I.1-isoform deficiency and mice with T cell-targeted I.1 knockdown. We found that genetic deletion of the I.1 isoform resulted in enhanced resistance to septic lethality, significantly reduced bacterial load in peripheral blood, increased M1 macrophage polarization, augmented levels of pro-inflammatory cytokines in serum, and significantly decreased levels of the anti-inflammatory cytokine IL-10. Our data suggest an immunosuppressive role of the I.1 isoform in T cells during bacterial sepsis that was previously unrecognized. We interpret these data as indicative that activation-inducible isoform I.1 hinders the contribution of T cells to the anti-bacterial response by affecting M1/M2 macrophage polarization and microbicidal function.